Dissection of Learning Opportunities and Obstacles While Learning Through Video Conferencing Platform (VCP) - During Covid 19 Lockdown - Jyoti; Khina Sharma; Jyoti Sarin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background- COVID 19 pandemic has influenced our lives in all the aspects, even the younger generationsare also not left untouched, specially their studies. Professional courses like nursing has integrated theorywith practical learning and due to the lock down situation both aspects of learning - theory as well asthe clinical learning are suffering. Though the teaching institutes have come up with the solutions likeonline lectures, using the video conferencing platform (VCP). This has expanded the horizon of traditionalclassroom. Though it is widely practiced in developed countries but in India it is still a new trend of learning.Purpose - of this study was to assess learner’s satisfaction level while learning through video conferencingplatform and various opportunities and obstacles learner’s faced were explored. Methods – nursing studentswere the participants and online self-reporting method was adopted for the data collection. Self-developedquestionnaire was completed by 138 participants and questionnaire had 36 items to respond on VideoConferencing Platform related to learner’s satisfaction, also opportunities & obstacles encountered whilelearning through VCP.Results – Majority (63%) of the participants were somewhat satisfied, learning through VCP and 26.1% werehighly satisfied. Observation of the opportunities were found to be better learning outcome – brainstormingstimulation, self-motivated learning, able to ask and clear doubts and lecture was reported to be captivating.Another opportunity reported was comfort while learning which included the learning in personal space,no compulsion of physical presence at teaching institute and freedom to choose which lecture to attend.Obstacles reported were related to the classroom environment where the chances avoiding questions andfooling the instructor was reported by majority participants, technical challenges like slow internet disturbedthe lecture and made it difficult to articulate lecture and also missed part of lecture. Other obstacles reportedwere decreased social interaction, participants found learning through VCP to be tiresome as compared totraditional classroom, connectivity issues disturbance create due to the surroundings. Association betweenthe course of study with satisfaction level, opportunities and obstacles were found to be significant, whereasthe association between the time spend on VCP was found to be significant only with obstacles.